Pedagogical Negotiation in AMPLIA Environment - Flores, Cecília (2003)
AMPLIA is an Intelligent Learning Multi-Agent Environment. It is designed to support training of diagnostic reasoning and modeling of domains with complex and uncertain knowledge. AMPLIA focuses on the medical area, where learner’s modeling tasks will consist of creating a Bayesian network for a problem the system will present. A pedagogic negotiation process (managed by an intelligent Mediator Agent) will treat the differences of topology and probability distribution between the model the learner built and the one built-in in the system. That negotiation process occurs between the agents that represent the expert knowledge domain and the agent that represents the learner knowledge. The possibility of using Bayesian networks to create knowledge representation allows the learner to visualize his/her ideas organization, create and test hypothesis.